Dukungan guru meningkatkan kepatuhan konsumsi tablet tambah darah pada remaja putri di Kota Bogor - Nuradhiani, Annisa; Briawan, Dodik; Dwiriani, Cesilia Meti (Jurnal Gizi dan Pangan, 2017)
The objective of this study were to analyze the effect of different compliance monitoring cards of iron supplementation and the determinants in female adolescents in Bogor. Design of this study was quasi experimental. There were 240 adolescent girls from 6 different schools in Bogor who participated and allocated into 3 groups: receiving either monitoring card from Health Department (M), monitoring card verified by teacher and parents (M+T), and monitoring card verified by teacher with additional information about anemia and iron supplementation (M+TP). The data of iron supplement consumption compliance, perception of iron supplementation, nutritional knowledge, motivation, parents and teacher support were collected. The results showed, that a significant difference on compliance level among the groups (p<0.05). The M+TP group had the highest compliance level. Weekly compliance rate was higher (15%) compared to compliance during which participants were menstruating. The most determining factor for compliance level was teacher support (p<0.05; OR=4.7; 95%CI;1.5-14.2). The developed monitoring cards can improve compliance of iron supplement consumption on female adolescents.